Strategies for Enhancing Employee Retention: A Qualitative Study on Modern Human Resource Management Practices - Agustinus Sri Wahyudi; Ahmad Yanuar Syauki; Sunaeni; Loso Judijanto; Mochamad Irfan (GoAcademica Research & Publishing, 2023)
Employee retention is a critical concern for organizations in today's dynamic business environment. This qualitative study explores the strategies employed by modern human resource management practices to enhance employee retention. Through in-depth interviews and thematic analysis, this research delves into the perspectives of HR professionals and employees to identify effective retention strategies. The findings highlight the importance of a holistic approach that encompasses talent development, work-life balance, and a supportive organizational culture. Furthermore, this study sheds light on the significance of ongoing communication and feedback mechanisms in retaining valuable employees. By illuminating these strategies, this research contributes to a deeper understanding of contemporary HR practices aimed at fostering employee retention.